Perspectives of Refugee Youth Experiencing Homelessness: A Qualitative Study of Factors Impacting Mental Health and Resilience - Khan, Bushra M.; Waserman, Jordana; Patel, Mitesh (Frontiers in Psychiatry, 2022)
Homeless refugee youth experience high rates of traumatic and adverse experiences, a significant burden of mental health needs, and compounded barriers in accessing support services. Despite this, there is a paucity of literature exploring the unique intersections and vulnerabilities faced by this subgroup. This study of Youth Without Shelter (YWS), an emergency residence and referral agency serving homeless youth in Toronto, Canada was a qualitative study of homeless refugee youth. Research goals were to describe the mental health needs and identify the factors contributing to the resiliency of refugee youth experiencing homelessness. Data was collected through individual semi-structured interviews with YWS youth (n=6) and analyzed using inductive thematic analysis with a realist lens. Results highlighted that the mental health of refugee youth experiencing homelessness was subject to system-level factors such as the immigration process (n=6), housing insecurity (n=5), finances (n=5), education (n=6), employment (n=6) and sense of safety (n=4), with acculturative stress, including culture shock (n=3) and language (n=4), also have negative effects. Goal directedness (n=5), independence or responsibility (n=4), and nurturing social connectedness with family (n=5), peers (n=6), and community (n=4) contributed to participants’ resilience. A model for future interventions is proposed where the focus would primarily be on immediate safety and security needs and subsequently, on long-term needs. Future efforts will be directed towards translating the lived experience of this population and developing practice guidelines to optimize care.